PENILAIAN KINERJA PELAYANAN PUBLIK PERMENPAN NO.25 TAHUN 2004 PADA P2T PEMPROV JATIM - Anggreyani, Novita (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the performance of technical implementation unit ofIntegrated Licensing Services of East Java Province which is measured by using General GuidelinePreparation of Community Satisfaction Index Government Agency Service Unit byKEP/25/M.PAN/2/2004 and to find out the suitability level between service performance andcommunity expectation or importance. Qualitative descriptive is used as the data analysis techniquein this research. Result of community satisfaction index calculation has found index 3.02 andCommunity Satisfaction Index is 75.57. Based on this value it can be concluded that the service qualityof technical implementation unit of Integrated Licensing Services of East Java Province is categorizedin good criteria âBâ. While the suitability level between community expectation or importance andperformance obtains 96.94% which means the service has already suitable with the communityexpectation. From 14 (fourteen) indicators of Community Satisfaction Index service elements areexplained in Cartesian diagram which consists of 4 quadrants: A Quadrant, B Quadrant, C Quadrant,and D Quadrant. The result of this Cartesian diagram there is a part which deserves to have attentionpriority in its handling which is service elements in A Quadrant is required to have first priority forservice performance improvement in the future, the certainty element of service schedule (serviceelement no. 12) and service duration (service element no. 7).Keywords: Community Satisfaction Index, Performance Assessment, Cartesian Diagram